2004
DOI: 10.1038/ng1309
|View full text |Cite
|
Sign up to set email alerts
|

SOX3 is required during the formation of the hypothalamo-pituitary axis

Abstract: The development of complex organs composed of different cell types frequently depends on reciprocal induction events occurring between distinct tissue layers that lie adjacent to one another in the embryo. The pituitary is a well studied case in point. It originates from two ectoderm-derived tissues, with the posterior lobe developing from an evagination of the ventral diencephalon, the infundibulum, and the intermediate and anterior lobes deriving from Rathke's pouch, an invaginating domain in the roof of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
280
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(299 citation statements)
references
References 35 publications
18
280
0
1
Order By: Relevance
“…Sox3 encodes a transcription factor that contains a conserved high-mobility group domain, which is a characteristic feature of the SOX transcription factor family, and its expression is conserved in the central nervous system of vertebrate embryos [35][36][37][38] . Also, in O. dancena, Sox3 expression was observed in adult brain, eye and gill tissues, but not in mature ovary or testis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sox3 encodes a transcription factor that contains a conserved high-mobility group domain, which is a characteristic feature of the SOX transcription factor family, and its expression is conserved in the central nervous system of vertebrate embryos [35][36][37][38] . Also, in O. dancena, Sox3 expression was observed in adult brain, eye and gill tissues, but not in mature ovary or testis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SOX3 should play significant roles in oogonium differentiation and oocyte development It has been suggested that SOX3 might play significant roles in sex determination and differentiation in vertebrates, but the evidence is insufficient and controversial (Graves 1998a;Pask et al 2000;Weiss et al 2003;Rizzoti et al 2004;Raverot et al 2005). Fish Physiol Biochem (2010) 36:181-193 187 One of the main causes might resulted from the difficulty in finding the exact cellular localization of SOX3 expression in the process of gametogenesis.…”
Section: Molecular Mechanisms On Sex Change In Groupersmentioning
confidence: 99%
“…However, the lethality of Sox2-null mutant mice at the preimplantation stage (Avilion et al 2003) combined with the overlap in expression and potential functional redundancy of the three highly related SOXB1 factors (SOX1, SOX2, and SOX3) in CNS progenitors (Collignon et al 1996;Pevny et al 1998;Weiss et al 2003;Rizzoti et al 2004;Tanaka et al 2004) have precluded genetic evaluation of the specific role of SOX2 in neural progenitor cells.…”
mentioning
confidence: 99%